The genus Oxyrhopus (Serpentes: Dipsadidae: Xenodontinae) in Guyana: morphology, distributions and comments on taxonomy - MacCulloch, Ross D.; Lathrop, Amy; Kok, Philippe J. R.; Ernst, Raffael; Kalamandeen, Michelle (Papéis Avulsos de Zoologia, 2009)
Considerable confusion exists regarding taxonomy and distributions of Oxyrhopus in northern South America. Specimens and records of Oxyrhopus from Guyana were examined. Oxyrhopus melanogenys, O. occipitalis and O. petola occur in Guyana. Data on morphology and colouration of these species are presented. Species distributions and characters to distinguish among the species are discussed.